The Effectiveness of the Contextual Teaching and Learning Model on Students’ Learning Outcomes in Islamic Religious Education - Saputri, Asyfaa Aulia; Baharudin, Baharudin; Selvia, Devi Sela Eka (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study aims to examine the effectiveness of the Contextual Teaching and Learning model on students’ learning outcomes in the Islamic Religious Education subject at SMP IT Bustanul ‘Ulum. This study was motivated by students’ low cognitive abilities, particularly at the analytical level, due to instruction that remains dominated by conventional methods. The study employed a quasi-experimental approach with a posttest-only control group design involving two classes: an experimental class and a control class, each consisting of 30 students. The experimental class received instruction using the Contextual Teaching and Learning model, while the control class used conventional methods. The research instrument was a multiple-choice test that had passed validity and reliability tests, with a reliability coefficient of 0.867. Data analysis using the Mann–Whitney test revealed a significance value of 0.000, which is less than 0.05, indicating a significant difference between the two groups. The results demonstrate that the Contextual Teaching and Learning model effectively improves students’ learning outcomes, particularly their analytical skills. This study contributes to the development of more contextual, active, and meaningful learning strategies for Islamic Religious Education.